Applications of ASR for the Optimization of Water Management - GUIGUER JUNIOR, NILSON; G. MALIVA, ROBERT; HERRMANN, ROLF (Águas Subterrâneas, 2012)
This paper describes three successful implementations of Aquifer Storage and Recovery (ASR) projects in different parts of the words, each one with a different objective. It demonstrates that ASR systems are capable of regulating water supply and demand with multiple benefits of traditional storage systems.